Comparison of cyclic fatigue resistance of XP-endo Shaper, HyFlex CM, FlexMaster and Race instruments - Mehmet Adiguzel; Ipek Isken; Ismail Ilker Pamukcu (Tabriz University of Medical Sciences, 2018)
Background. The aim of this study was to compare the cyclic fatigue resistance of XP-endo Shaper, HyFlex CM, FlexMaster and Race rotary instruments at body temperature (37±1°C). Methods. Twenty XP-endo Shaper (#30/.01), 20 HyFlex CM (#30/.04), 20 FlexMaster (#30/.04) and 20 Race (#30/.04) instruments were tested at body temperature (n=20). The instruments were evaluated in artificial canals with a 3-mm radius of curvature and 60° angle of curvature to the center of the 1.5-mm-wide canal. Each instrument was rotated until fracture occurred and the number of cycles to failure (NCF) recorded. Data were analyzed using one-way ANOVA and Tukey HSD tests (P<0.05). Results. The difference in the NCF of all the instruments was statistically significant (P<0.05). The order of the instruments from the highest to the lowest NCF was as follows: XP-endo Shaper (3064.0±248.1), HyFlex CM (1120.5±106.1), FlexMaster (569.8±48.4) and Race (445.5±53.5). Conclusion. Under the limitations of the present study, XP-endo Shaper instruments were more resistant to cyclic fatigue than the #30/.04 nickel-titanium rotary instruments immersed in water at simulated body temperature. Key words: Body temperature, cyclic fatigue, FlexMaster, HyFlex CM, Race, XP-endo Shaper.